2019
DOI: 10.3390/su11123308
|View full text |Cite
|
Sign up to set email alerts
|

Gardeners’ Past Gardening Experience and Its Moderating Effect on Community Garden Participation

Abstract: Studies on participation in community gardens have revealed that gardeners’ participation is driven by functional and emotional motives. Most studies, however, have failed to recognize gardeners’ diverse characteristics. To fill this research gap, this study examined the moderating effect that variations within gardeners has on their participation, particularly as in the case of past gardening experience. The data for this study were obtained through a survey administered in three plot-based community gardens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
(96 reference statements)
1
9
0
Order By: Relevance
“…In our study, gardening experience positively impacted community gardens, with respondents with gardening experience almost always supportive of community gardens, and previous research has similarly shown that increased gardening experience enhances the impact of affective motivation on gardening participation (Lee and Matarrita-Cascante, 2019). However, those who engage in home gardening prefer to build community gardens, which are a reflection of demand, and community gardens provide a place for gardening activities.…”
Section: Discussionsupporting
confidence: 58%
“…In our study, gardening experience positively impacted community gardens, with respondents with gardening experience almost always supportive of community gardens, and previous research has similarly shown that increased gardening experience enhances the impact of affective motivation on gardening participation (Lee and Matarrita-Cascante, 2019). However, those who engage in home gardening prefer to build community gardens, which are a reflection of demand, and community gardens provide a place for gardening activities.…”
Section: Discussionsupporting
confidence: 58%
“…According to Stedman [25,28], place meanings are cognitions people hold towards certain places, and represent a descriptive statement of what a place means. Humans attribute symbolic meanings to a place based on their cognition, and further develop a positive emotional or affective bond to it [23,48]. In this study, Discovery Green was an important everyday place which local families and individuals often visited.…”
Section: Research Findings Discussionmentioning
confidence: 88%
“…Previous work has suggested that access to community gardens can help immigrant communities maintain cultural ties and adjust to a new country (Hartwig and Mason, 2016; Hondagneu‐Sotelo, 2015). Immigrants are often more familiar with growing food than other garden participants (Cohen and Reynolds, 2015; Lee and Matarrita‐Cascante, 2019; Minkoff‐Zern, 2012). Thirteen of the gardens have a significant number of gardeners from one or more ethnic groups.…”
Section: Resultsmentioning
confidence: 99%